Reduced Vrk2 expression is associated with higher risk of depression in humans and mediates depressive-like behaviors in mice - Mei-Yu Yin; Lei Guo; Li-Juan Zhao; Chen Zhang; Wei-Peng Liu; Chu-Yi Zhang; Jin-Hua Huo; Lu Wang; Shi-Wu Li; Chang-Bo Zheng; Xiao Xiao; Ming Li; et al. (BMC Medicine, 2023)
Abstract Background Genome-wide association studies (GWAS) have reported single-nucleotide polymorphisms (SNPs) in the VRK serine/threonine kinase 2 gene (VRK2) showing genome-wide significant associations with major depression, but the regulation effect of the risk SNPs on VRK2 as well as their roles in the illness are yet to be elucidated. Methods Based on the summary statistics of major depression GWAS, we conducted population genetic analyses, epigenome bioinformatics analyses, dual luciferase reporter assays, and expression quantitative trait loci (eQTL) analyses to identify the functional SNPs regulating VRK2; we also carried out behavioral assessments, dendritic spine morphological analyses, and phosphorylated 4D-label-free quantitative proteomics analyses in mice with Vrk2 repression. Results We identified a SNP rs2678907 located in the 5’ upstream of VRK2 gene exhibiting large spatial overlap with enhancer regulatory marks in human neural cells and brain tissues. Using luciferase reporter gene assays and eQTL analyses, the depression risk allele of rs2678907 decreased enhancer activities and predicted lower VRK2 mRNA expression, which is consistent with the observations of reduced VRK2 level in the patients with major depression compared with controls. Notably, Vrk2 −/− mice exhibited depressive-like behaviors compared to Vrk2 +/+ mice and specifically repressing Vrk2 in the ventral hippocampus using adeno-associated virus (AAV) lead to consistent and even stronger depressive-like behaviors in mice. Compared with Vrk2 +/+ mice, the density of mushroom and thin spines in the ventral hippocampus was significantly altered in Vrk2 −/− mice, which is in line with the phosphoproteomic analyses showing dysregulated synapse-associated proteins and pathways in Vrk2 −/− mice. Conclusions Vrk2 deficiency mice showed behavioral abnormalities that mimic human depressive phenotypes, which may serve as a useful murine model for studying the pathophysiology of depression.